Pelatihan Pengembangan Suplemen Kurikulum Merdeka Berbasis Kearifan Lokal bagi Guru SD Kota Malang - Ni Luh Sakinah Nuraini; Puri Selfi Cholifah; Silva Nabilla; Misye Agustin Tri Wahyuni; Rifdah Afifah; Davina Aurelia; Ni Luh Sakinah Nuraini; Puri Selfi Cholifah; Silva Nabilla; Misye Agustin Tri Wahyuni; Rifdah Afifah (Universitas Negeri Malang, 2023)
Abstract: The initial study was conducted on one of the partners of the PGSD department of the State University of Malang, namely a state elementary school in Malang City. Initial studies have been carried out in the Teaching Material Development Training scheme, in general, on the collection of teaching module assignments only completed by about 60 percent of participants. During spontaneous interviews at the activity, data showed that teachers found it difficult to implement the Independent Curriculum. Based on the assessment of partner needs and problems, the solution to solving these needs is to hold training. The proposer team initiated an activity, namely